The Glutathione System and its Regulation by Neurohormone Melatonin in the Central Nervous System - H. Limon-Pacheco, Jorge; E. Gonsebatt, Maria (Central Nervous System Agents in Medicinal Chemistry, 2010)
The glutathione system includes reduced (GSH) and oxidized (GSSG) forms of glutathione; the enzymes required for its synthesis and recycling, such as gamma-glutamate cysteine ligase (γ-GCL), glutathione synthetase (GS), glutathione reductase (GSR) and gamma glutamyl transpeptidase (γ-GGT); and the enzymes required for its use in metabolism and in mechanisms of defense against free radical-induced oxidative damage, such as glutathione s-transferases (GSTs) and glutathione peroxidases (GPxs). Glutathione functions in the central nervous system (CNS) include maintenance of neurotransmitters, membrane protection, detoxification, metabolic regulation, and modulation of signal transduction. A common pathological hallmark in various neurodegenerative disorders, such as amyotrophic lateral sclerosis and Alzheimer's and Parkinson's diseases, is the increase in oxidative stress and the failure of antioxidant systems, such as the decrease in the GSH content. The administration of exogenous neurohormone melatonin at pharmacological doses has been shown not only to be an effective scavenger of reactive oxygen and nitrogen species but also to enhance the levels of GSH and the expression and activities of the GSH-related enzymes including γ-GCL, GPxs, and GSR. The exact mechanisms by which melatonin regulates the glutathione system are not fully understood. The main purpose of this short review is to discuss evidence relating to the potential common modulation signals between the glutathione system and melatonin in the CNS. The potential regulatory mechanisms and interactions between neurons and non-neuronal cells are also discussed.
Keywords: p38 kinase